The Effect of Murabahah, Mudharabah, Musharakah and Ijarah Financing on The Level of Net Profit - Echamawaty, Sefty; Safira (Baca Dulu Publisher, 2024)
This research aims to examine the effect of financing murabahah, mudharabah, musyarakah and ijarah of towards the level net profit. This research was conducted on companies registered in Islamic Commercial Banks. The population in this study amounted to 13 companies in the period 2012-2017. Samples were taken using purposive sampling method. Samples that meet the criteria of 5 companies. Data analysis method uses multiple linear regression analysis. The results of this research indicate that the financing murabahah and financing mudharabah are significant effect on the towards the level net profit, while financing musyarakah and financing ijarah no significant effect on towards the level net profit registered in Islamic Commercial Banks.